ANALISIS KANDUNGAN FLAVONOID EKSTRAK ETANOL DEKLOROFILASI DAUN KENIKIR (Cosmos caudatus) - Masmor, Elvira; Abidin, Zainal; Razak, Rais (PHARMACY UMI JOURNAL SYSTEM, 2024)
Kenikir leaves (Cosmos caudatus) from the Asteraceae family, is a family that is widely used as herbal medicine. Kenikir leaves are usually used as vegetables or fresh vegetables. Kenikir leaves (Cosmos caudatus) are also used as an ulcer medicine, boost the body's immune system, strengthen bones, increase appetite, and overcome bad breath. The purpose of this study was to conduct a research on the analysis of flavonoids in the dechlorophyllated extract of kenikir (Cosmos caudatus) leaves by UV-Vis spectrophotometer. The use of the dechlorophyllated extract method of kenikir (Cosmos caudatus) leaves to remove chlorophyll in the leaves, and this method has never been applied to extracts with other organic solvents. This method has the potential to be developed in efforts to remove chlorophyll from leaf extracts. The results obtained by dechlorophyllated extract of kenikir leaves (Cosmos caudatus) on UV-Vis spectrophotometry were identified to contain flavonoid compounds, with an ethanolic flavonoid content of 63.0833 mgQE/g extract, and a dechlorophyllated extract with a flavonoid content of 105.283 mgQE/g.